Nanang: A short feature film - Apacible, Sophia Angela M. (Animo Repository, 2021)
NANANG is a 15- minute feature film that revolves around both the simple and privileged lifestyles of a Manila based student and a farmer from Benguet through the lives of Solana and Rose. How each of them react and behave to the different activities and encounters in the story, and the development of their relationship which results in their awakening and self-realization. NANANG tells the story of Solana, a privileged, “maarte”, high school student who at the last minute, decides to join her school’s immersion program in Tuba, Benguet where she is to live with a farmer for one week. Here she is paired with Rose, a 55 year old farmer who at first did not want to participate in the immersion program. She is the opposite of Solana, introverted, closed-off and shy. The two create an unexpected bond during their week together and learn from one another. Their stories shed light on the problems farmers face and the start of their friendship which will change both of their perspectives on life. The thesis proponents opted to reimagine their thesis due to the health risks of the COVID-19 pandemic. The short film’s story is told through a screenplay, a series of visual pegs, posters and a marketing plan for the post-production of the film when it is safe to film it in person.